2014
DOI: 10.3390/min4020241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the November 2012 Flood Event on the Mobilization of Hg from the Mount Amiata Mining District to the Sediments of the Paglia River Basin

Abstract: The Mount Amiata mining district (southern Tuscany, Italy) was, for decades, one of the world's largest mercury (Hg) producing regions, where mining activity lasted until the 1980s. The Paglia River drains the eastern part of the district and is also the main western tributary of the Tiber River. Recent studies show that, still today, high total Hg contents severely affect the downstream ecosystems of these rivers. In November 2012, a major flood event occurred in the Paglia River basin, which drastically chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…As previously noted, a major flood event occurred along the Paglia R. in February 2016. A comparison was made between the Hg concentrations of the overbank deposits of this event, and the deposits of baseflow channel, bar, and floodplain (Table 5), to ascertain whether this event caused an important remobilization of Hg-contaminated sediments, as demonstrated by Pattelli et al (2014) for the November 2012 event.…”
Section: The Flood Event Of February 2016mentioning
confidence: 99%
See 3 more Smart Citations
“…As previously noted, a major flood event occurred along the Paglia R. in February 2016. A comparison was made between the Hg concentrations of the overbank deposits of this event, and the deposits of baseflow channel, bar, and floodplain (Table 5), to ascertain whether this event caused an important remobilization of Hg-contaminated sediments, as demonstrated by Pattelli et al (2014) for the November 2012 event.…”
Section: The Flood Event Of February 2016mentioning
confidence: 99%
“…In most cases, the Hg concentrations of 2016 overbank flood Table 5 Hg concentration values of baseflow channel (C), bar (B) and floodplain (FP) collected in 2013, and of the overbank deposits of the February 2016 flood. -No data.°( After Pattelli et al, 2014; in parentheses, their sample label is reported). * = mean value between the two banks.…”
Section: The Flood Event Of February 2016mentioning
confidence: 99%
See 2 more Smart Citations
“…Mining waste management includes the characterization and remediation of residues. The state-of-the-art proposes new methods such as the use of mapping to determine the extent of wastes, the use of hyperspectral instruments [25], the mobility of sediments containing toxic residues [26], the mitigation of toxic metals spread in redox areas [27], the use of biochemical and mineral dissolution processes in sulfurous tailings [28], the dilution of tailings products, and the geochemical and mineral elimination of submarine tailings [29]. Other remediation systems include the use of heat to volatilize toxic components, and the use of microorganisms to reduce the reactivity and toxicity [30].…”
Section: Introductionmentioning
confidence: 99%